2018
DOI: 10.3389/fpsyg.2018.00203
|View full text |Cite
|
Sign up to set email alerts
|

Gray Matter Volume of a Region in the Thalamic Pulvinar Is Specifically Associated with Novelty Seeking

Abstract: Personality reflects the set of psychological traits and mechanisms characteristic for an individual. Geno-neuro-biologically inspired personality accounts have proposed a set of temperaments and characters that jointly compose personality profiles. The present study addresses the link between neurobiology and personality and investigates the association between temperament traits and regional gray matter volume. Furthermore, the specificity of these associations as well as the underlying components that drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…Also, a separate study of a similar sample size to our present study (56 subjects) but with much lower mean NS score (10.4 ± 3.5), reports a posi�ve correla�on between NS with the le� middle frontal gyrus volume irrespec�ve to gender (Iidaka et al, 2006). A third study with similar NS scores as this one (17.9 ± 6.167) reports a posi�ve associa�on between NS and the le� thalamic pulvinar regions (Stam et al, 2018) but the sample size was confounded by inclusion of first degree rela�ves of pa�ents Hun�ngton disease and an uneven balance of male and female par�cipants. It is also worth no�ng that in the present study, our par�cipant exclusion criteria included drug usage, tobacco smoking and excessive alcohol consump�on, all factors that might increase novelty-seeking (Addicot et al, 2014;Wingo et al, 2016).…”
Section: Main Findingssupporting
confidence: 74%
“…Also, a separate study of a similar sample size to our present study (56 subjects) but with much lower mean NS score (10.4 ± 3.5), reports a posi�ve correla�on between NS with the le� middle frontal gyrus volume irrespec�ve to gender (Iidaka et al, 2006). A third study with similar NS scores as this one (17.9 ± 6.167) reports a posi�ve associa�on between NS and the le� thalamic pulvinar regions (Stam et al, 2018) but the sample size was confounded by inclusion of first degree rela�ves of pa�ents Hun�ngton disease and an uneven balance of male and female par�cipants. It is also worth no�ng that in the present study, our par�cipant exclusion criteria included drug usage, tobacco smoking and excessive alcohol consump�on, all factors that might increase novelty-seeking (Addicot et al, 2014;Wingo et al, 2016).…”
Section: Main Findingssupporting
confidence: 74%
“…13,65 A recent study including premanifest HD patients found novelty seeking, a measure of impulsivity, was correlated with structural differences in the left thalamic pulvinar. 66 Notably, work in PD has associated different dimensions of impulsivity with specific altered network connectivity patterns on diffusion imaging, which again correspond to regions implicated in apathy and crucial for normal goal-directed behavior. 67 Such characterization of impulsivity dimensions and their neural correlates remains to be investigated in people with HD.…”
Section: Neural Correlates Of Impulsivity and Apathy In Hd Overlapmentioning
confidence: 98%
“…Failed response inhibition in premanifest HD patients as well as disinhibition and pathological impulses in HD are associated with altered activation in very similar brain regions 13,65 . A recent study including premanifest HD patients found novelty seeking, a measure of impulsivity, was correlated with structural differences in the left thalamic pulvinar 66 . Notably, work in PD has associated different dimensions of impulsivity with specific altered network connectivity patterns on diffusion imaging, which again correspond to regions implicated in apathy and crucial for normal goal‐directed behavior 67 .…”
Section: Neural Correlates Of Impulsivity and Apathy In Hd Overlapmentioning
confidence: 99%
“…Several studies have investigated the associations between temperaments and regional GMv (Iidaka et al, 2006; Gardini et al, 2009; Picerni et al, 2013; Laricchiuta et al, 2014; Stam et al, 2018). However, sex is a variable that is typically statistically controlled for and little is known about its effect on temperament-brain associations.…”
Section: Introductionmentioning
confidence: 99%